Preparation method of positive electrode material-manganese-based catalyst of alkaline aluminum-air battery

By using low-cost manganese-based catalysts, high-active sites are formed using materials such as methylcellulose aerogel and g-C3N4, the problem of slow kinetics of oxygen reduction reaction in alkaline aluminum air batteries is solved, and a high-efficiency and low-cost catalytic effect is achieved.

CN119812368APending Publication Date: 2025-04-11TONGREN UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510211973.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-25
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Alkaline aluminum air batteries are difficult to promote on a large scale due to their slow kinetics, high overpotentials, and relying on expensive and precious metal catalysts (such as Pt/C).

Method used

Using a low-cost manganese-based catalyst, a composite system of methylcellulose aerogel, g-C3N4, conductive carbon black and manganese dioxide is formed to form a highly active Mn-Nx site, significantly improving the catalytic activity of the oxygen reduction reaction.

Benefits of technology

The oxygen reduction reaction rate has been improved, the raw material cost has been reduced, and it is suitable for industrial production. The performance of the catalyst is close to that of the precious metal catalyst, breaking through the performance bottleneck of traditional non-precious metal catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812368A_ABST
    Figure CN119812368A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and particularly discloses a preparation method of a manganese-based catalyst serving as a positive electrode material of an alkaline aluminum-air battery. The manganese-based catalyst is prepared by mixing manganese dioxide, g-C3N4, conductive carbon black and methylcellulose aerogel and then performing heat treatment through a tubular furnace. The half-wave potential of the prepared manganese-based catalyst (MCA-Mn-N-C) is 0.8862 V (vs.RHE), and the limiting current of the prepared manganese-based catalyst (MCA-Mn-N-C) is 4.4552 mA cm <-2 >. The prepared aluminum air battery catalyst is high in catalytic activity, simple in preparation method and low in cost. The catalyst provided by the invention aims to promote the oxygen reduction reaction of the positive electrode of the alkaline aluminum-air battery and improve the overall battery performance of the alkaline aluminum-air battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and in particular relates to a method for preparing a positive electrode material-a manganese-based catalyst of an alkaline aluminum-air battery. Background Art

[0002] Aluminum is the most abundant metal on earth, and aluminum-air battery is a new type of energy battery. It uses aluminum as the negative electrode and the air electrode as the positive electrode, and generates electricity by consuming aluminum and oxygen in the air. As a metal-air battery with high energy density, aluminum-air battery has the characteristics of low cost, good safety, no combustion and explosion, and no environmental pollution. It is one of the research hotspots of new energy storage devices. Oxygen reduction reaction is the core reaction on the air electrode of aluminum-air battery. Inevitably, aluminum-air battery, like other metal-air batteries, has problems such as slow reaction kinetics, high overpotential, and complex reaction mechanism in the oxygen reduction process, which is one of the main factors hindering the development of aluminum-air battery. One of the ways to solve this problem is to develop efficient catalysts.

[0003] The development of effective oxygen reduction catalysts can significantly increase the oxygen reduction reaction rate, increase the reaction current density, and improve the overall performance of aluminum-air batteries. Currently, the known catalyst with good ORR catalytic activity is Pt / C catalyst, but the high cost of Pt / C catalyst is not conducive to large-scale promotion. Therefore, the development of a low-cost, high-performance, and easy-to-prepare catalyst can effectively promote aluminum-air batteries. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a positive electrode material-manganese-based catalyst for an alkaline aluminum-air battery, to promote the oxygen reduction process of the positive electrode of the alkaline aluminum-air battery, to accelerate the rate of its oxygen reduction reaction process, and to improve the overall performance of the aluminum-air battery.

[0005] To achieve the above technical objectives, the technical solution adopted by the present invention is as follows: A method for preparing a positive electrode material of an alkaline aluminum-air battery-manganese-based catalyst comprises the following steps:

[0006] (1) Preparation of methylcellulose aerogel: pour methylcellulose slowly and repeatedly in small amounts into water, stir evenly, put it into a refrigerator for pre-freezing after gelation, and freeze-dry it after pre-freezing to obtain methylcellulose aerogel;

[0007] (2) Preparation of g-C3N4: Weigh melamine and pour it into a porcelain boat. Place the porcelain boat in a tube furnace for heat treatment. After heat treatment, cool to room temperature. Transfer the product in the porcelain boat into a mortar and grind it evenly to obtain g-C3N4.

[0008] (3) Preparation of manganese-based catalyst: The prepared methyl cellulose aerogel was spread on the bottom of a porcelain boat, and then g-C3N4, manganese dioxide, and conductive carbon black were ground and mixed evenly, spread on the methyl cellulose aerogel, and then placed in a tubular furnace for heat treatment;

[0009] (4) Grinding the heat-treated catalyst to obtain a manganese-based catalyst.

[0010] Optionally, in step (1), the gelation time is 1 day, the pre-freezing time is 3 days, and the drying time is 2 days.

[0011] Optionally, in step (2), the heat treatment conditions in the tube furnace are: heating to 550° C. at a heating rate of 5° C. / min and then maintaining the temperature for 4 hours.

[0012] Preferably, in step (3), the mass ratio of methyl cellulose aerogel: g-C3N4: manganese dioxide: conductive carbon black is 2:2:1:1.

[0013] Optionally, in step (3), the heat treatment conditions in the tubular furnace are: the tubular furnace is heated to 800° C. at a heating rate of 5° C. / min and then maintained at a constant temperature for 2 hours.

[0014] Optionally, in step (3), argon gas needs to be continuously introduced into the tubular furnace during the heat treatment process.

[0015] Optionally, in step (1), the obtained methyl cellulose aerogel is cut into thin slices weighing 0.2 g.

[0016] As described above, the present invention solves the technical difficulties in the prior art that alkaline aluminum-air batteries are difficult to promote on a large scale due to slow oxygen reduction reaction (ORR) kinetics, high overpotential, and reliance on expensive precious metal catalysts (such as Pt / C). The breakthrough is achieved through the following technical measures: (1) Design of low-cost manganese-based catalyst: a composite system of manganese dioxide, g-C3N4, conductive carbon black, and methyl cellulose aerogel is used. The high specific surface area and pore structure of methyl cellulose aerogel provide a carrier for Mn atoms to embed into the nitrogen-doped carbon skeleton, forming a highly active Mn-N x (2) Optimization of preparation process: Through the step-by-step pyrolysis process (such as synthesizing g-C3N4 at 550°C and heat treating the composite at 800°C in an argon atmosphere), the precise control of the catalyst structure and composition is achieved, while simplifying the preparation process and reducing costs.

[0017] An alkaline aluminum-air battery comprises a full battery, an alkaline electrolyte and a peristaltic pump, wherein the full battery comprises a battery fixture, the battery fixture comprises a sealing rubber gasket, a reaction chamber, and a battery template, wherein the reaction chamber is formed into a whole by a liquid inlet pipe, a reaction chamber and a liquid outlet pipe; the sealing rubber gasket is attached to both sides of the reaction chamber, and an aluminum sheet and a positive electrode film are attached to the sealing rubber gasket, and the battery template is closed to complete a full battery assembly;

[0018] The alkaline electrolyte is stored in an electrolyte storage tank and connected to a peristaltic pump through a circulation pipe;

[0019] The circulation pipe is connected with the liquid inlet pipe and the liquid outlet pipe;

[0020] The positive electrode membrane is composed of a waterproof breathable membrane, a nickel mesh, a waterproof breathable membrane and a catalyst layer from bottom to top, wherein the catalyst layer is a manganese-based catalyst prepared by the aforementioned preparation method.

[0021] Optionally, the alkaline electrolyte is 4 mol·L -1 of NaOH solution.

[0022] Optionally, the preparation of the positive electrode film comprises the following steps:

[0023] (1) Weigh the corresponding materials according to the mass ratio of manganese-based catalyst: conductive carbon black: activated carbon: polytetrafluoroethylene emulsion = 2:1:4:3, first grind the manganese-based catalyst, conductive carbon black and activated carbon in a mortar evenly, then add anhydrous ethanol with a similar dry matter weight to disperse evenly, then drop the polytetrafluoroethylene emulsion into it, grind it with a grinding rod, and obtain a dough-like catalyst material with a smooth surface;

[0024] (2) Pressing the dough-like catalyst material into a 0.1-0.15 mm film and drying it to form a catalyst layer;

[0025] (3) stacking the waterproof breathable membrane, nickel mesh, waterproof breathable membrane and catalyst layer from bottom to top, and pressing them into a 0.3 mm positive electrode membrane using a double roller machine;

[0026] (4) The positive electrode film is placed in an oxygen-free environment and subjected to high temperature treatment at 300° C. for 1-3 hours.

[0027] Compared with the prior art, the present invention has at least the following advantages:

[0028] (1) Aluminum is the most abundant metal resource on earth, and manganese is also a relatively abundant metal resource, so its raw material cost is relatively low. This makes alkaline aluminum-air batteries have certain advantages in cost and resources. The present invention replaces precious metal platinum with abundant manganese, combined with cheap methyl cellulose aerogel, greatly reduces the raw material cost and is suitable for industrial production.

[0029] (2) The manganese-based catalyst of the present invention can embed Mn atoms into the nitrogen-doped carbon skeleton at high temperature due to the high specific surface area and good pore structure of the methylcellulose aerogel to form Mn-N x Highly active sites can effectively promote the oxygen reduction reaction process of the positive electrode of alkaline aluminum-air batteries. The ORR catalytic efficiency is close to that of precious metal catalysts, breaking through the performance bottleneck of traditional non-precious metal catalysts.

[0030] (3) The process of the present invention is simple and scalable, the preparation steps are concise (such as freeze drying and tubular furnace heat treatment), no complicated equipment or harsh conditions are required, it is easy to apply on a large scale, and has certain commercial prospects.

[0031] (4) Superior overall battery performance: The optimized design of the catalytic layer and battery structure enables the battery to have high energy density, stable discharge capacity and long cycle life, promoting the practical application of aluminum-air batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The present invention is further illustrated by means of the non-limiting examples given in the accompanying drawings.

[0033] Figure 1 This is a reaction mechanism diagram of the alkaline aluminum-air battery prepared in Example 1 of the present invention.

[0034] Figure 2 This is a photo of the alkaline aluminum-air battery prepared in Example 1 of the present invention.

[0035] Figure 3 It is a schematic diagram of the full battery structure of the present invention.

[0036] Figure 4 Schematic diagram of the cathode membrane structure of the present invention.

[0037] Figure 5 This is the ORR test curve of the manganese-based catalyst (MCA-Mn-NC) prepared in Example 2 of the present invention.

[0038] Figure 6 This is a graph showing the half-wave potential and limiting current of the manganese-based catalyst (MCA-Mn-NC) prepared in Example 2 of the present invention.

[0039] Figure 7 This is the CV test curve of the manganese-based catalyst (MCA-Mn-NC) prepared in Example 2 of the present invention.

[0040] Figure 8 This is a test curve of the relative stability rate of the it catalyst of the manganese-based catalyst (MCA-Mn-NC) prepared in Example 2 of the present invention.

[0041] Fig. 9The power density and polarization curve of the alkaline aluminum-air battery prepared in Example 1 of the present invention.

[0042] Fig.10 This is the capacity density curve of the alkaline aluminum-air battery prepared in Example 1 of the present invention after 1h constant current discharge.

[0043] Fig.11 This is the cycle curve of the alkaline aluminum-air battery prepared in Example 1 of the present invention.

[0044] Fig.12 This is a step discharge curve of the alkaline aluminum-air battery prepared in Example 1 of the present invention.

[0045] Description of reference numerals:

[0046] 1-battery fixture, 2-aluminum sheet, 3-sealing rubber gasket, 4-positive electrode membrane. DETAILED DESCRIPTION

[0047] In order to enable those skilled in the art to better understand the present invention, the technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0048] Embodiment 1:

[0049] An alkaline aluminum-air battery, such as Figure 1-3 As shown, it includes a full battery, an alkaline electrolyte and a peristaltic pump, wherein the full battery includes a battery fixture 1, the battery fixture 1 includes a sealing rubber gasket 3, a reaction chamber, and a battery template, and the reaction chamber is composed of a liquid inlet pipe, a reaction chamber and a liquid outlet pipe to form a whole; the sealing rubber gasket 3 is adhered to both sides of the reaction chamber, and the aluminum sheet 2 and the positive electrode film 4 are adhered to the sealing rubber gasket 3, and the battery template is closed to complete a full battery assembly.

[0050] The alkaline electrolyte is stored in an electrolyte storage tank, the number of the electrolyte storage tank is one, and the electrolyte storage tank is connected to the peristaltic pump through a circulation pipe;

[0051] The circulation pipe is communicated with the liquid inlet pipe and the liquid outlet pipe.

[0052] like Figure 4 As shown, it is a schematic diagram of the structure of the positive electrode membrane, which consists of a waterproof and breathable membrane, a nickel mesh, a waterproof and breathable membrane and a catalyst layer from bottom to top.

[0053] Embodiment 2:

[0054] The steps for preparing the catalyst in the catalytic layer described in the above-mentioned Example 1 are as follows:

[0055] (1) Preparation of methylcellulose aerogel: Weigh 3 g of methylcellulose and slowly add it to a beaker containing 50 mL of water several times, stirring while pouring. After mixing evenly, let it stand. After gelation for one day, transfer it to a watch glass and put it in an ultrasonic cleaner for 30 minutes to remove bubbles in the gel. Put the methylcellulose gel with bubbles removed into a refrigerator for pre-freezing for 3 days, and then put it into a freeze dryer for drying for 2 days. After drying, methylcellulose aerogel is obtained. The dried methylcellulose aerogel is cut into thin slices weighing 0.2 g.

[0056] (2) Preparation of g-C3N4: Weigh 5 g of melamine and put it into a porcelain boat, then place the porcelain boat into a tube furnace for heat treatment. The tube furnace heat treatment conditions are to increase the temperature to 550°C at a rate of 5 min / °C and then keep the temperature constant for 4 hours. After cooling to room temperature, transfer the product in the porcelain boat into a mortar and grind it evenly to obtain g-C3N4 powder.

[0057] (3) Preparation of manganese-based catalyst: Spread the prepared methyl cellulose aerogel sheet on the bottom of a porcelain boat, weigh the materials in a mass ratio of methyl cellulose aerogel: g-C3N4: manganese dioxide: conductive carbon black of 2:2:1:1, mix and grind them evenly, spread them evenly on the methyl cellulose aerogel sheet, so that the material mixture completely covers the gel sheet, and then transfer them to a tube furnace for heat treatment. Argon needs to be continuously introduced during the heat treatment process. The heat treatment conditions are to increase the temperature to 800°C at 5°C / min and keep the temperature constant for 2h. After cooling to room temperature, transfer the product in the porcelain boat to a mortar and grind it evenly to obtain a manganese-based catalyst (MCA-Mn-NC).

[0058] Embodiment 3:

[0059] The steps for preparing the positive electrode film described in the above-mentioned embodiment 1 are as follows:

[0060] (1) According to the mass ratio of manganese-based catalyst (prepared in Example 2): conductive carbon black: activated carbon: polytetrafluoroethylene emulsion (PTFE emulsion) = 2:1:4:3, the corresponding materials are weighed, the manganese-based catalyst, conductive carbon black and activated carbon are firstly ground evenly in a mortar, and then anhydrous ethanol with a similar dry matter weight is added to disperse them evenly, and then the polytetrafluoroethylene emulsion is dropped into it, and ground with a grinding rod to obtain a dough-like catalyst material with a smooth surface.

[0061] (2) Press the dough-like catalyst material into a 0.1-0.15 mm film and dry it to form a catalyst layer.

[0062] (3) The waterproof breathable membrane, nickel mesh, waterproof breathable membrane and catalytic layer are pressed Figure 4 The structures are stacked in sequence and pressed into a positive electrode film of about 0.3 mm using a double-roller machine.

[0063] (4) The positive electrode membrane is placed in an oxygen-free environment at 300°C for about 1-3 hours, and the treatment time is determined according to the number of membranes. For example, five positive electrode membranes (length and width are 9 cm×3 cm) are prepared in the present invention and treated at high temperature for 1 hour.

[0064] Embodiment 4:

[0065] The steps for preparing the alkaline electrolyte described in the above-mentioned embodiment 1 are as follows:

[0066] Weigh 32 g of sodium hydroxide and dissolve it in 200 mL of water to prepare a 4 M NaOH solution, and cool it to room temperature to obtain an alkaline electrolyte.

[0067] The catalyst (MCA-Mn-NC) prepared in Example 2 was subjected to ORR test ( Figure 5 , Figure 6 ), CV test( Figure 7 ), it stability test( Figure 8 ). Figure 5-Figure 8 The electrochemistry of the electrode was tested by a rotating disk electrode device in an environment with 0.1M KOH electrolyte and continuous oxygen flow. Figure 5 , Figure 6 and Figure 8 It is also necessary to test at 1600rpm. Figure 7 The CV test was performed at 0 rpm as a static test.

[0068] like Figure 5 , Figure 6 As shown, the catalyst ORR test range is 1.14V (vs. RHE)-0.44V (vs. RHE), by reading Figure 5 The ORR curve at 1.09 V (vs. RHE) and 0.54 V (vs. RHE) can be used to calculate the half-wave potential of the catalyst. At the same time, the limiting current read at 0.54 V (vs. RHE) shows that the half-wave potential and limiting current of the manganese-based catalyst (MCA-Mn-NC) are 0.8862 V and 4.4552 mA cm, respectively. -2 The half-wave potential and limiting current of Pt / C are 0.8972 V and 4.476 mA cm -2 near.

[0069] like Figure 7 As shown, the CV test voltage range of the catalyst is 1.634V (vs.RHE)-0.492V (vs.RHE), and an oxygen reduction peak appears at a potential of 1.121V (vs.RHE), indicating that the catalyst can undergo oxygen reduction reaction at 1.121V (vs.RHE).

[0070] like Figure 8As shown, the stability of the catalyst was tested using the chronoamperometry method. After excluding the unstable voltage in the first 1000 seconds, the current decay of the catalyst at a voltage of -0.5V (vs. SCE) was calculated to determine the stability of the catalyst. Figure 8 It shows that the catalyst still has 81.69% stability at 11000s.

[0071] Figure 9-12 This is a full battery test performed on the Shanghai Chenhua electrochemical workstation. Figure 2 Alkaline aluminum-air battery assembled for testing.

[0072] like Fig. 9 The figure shows an LSV test of the full battery, with a test voltage range of 0V (vs. SCE)-2V (vs. SCE). This test reflects the power density and polarization curve of the full battery. The overall power density of the full battery is 60.88mW cm -2 .

[0073] like Fig.10 The figure shows the change in capacity density of the whole battery after constant current discharge. The constant current test was conducted at 20 mA for 1 hour. The mass difference of the aluminum block before and after discharge was calculated to reflect the capacity density of the whole battery. It can be seen that the capacity density of the whole battery at 20 mA is 1307.55 mAh g -1 .

[0074] like Fig.11 The figure shows a full battery cycle discharge test. After testing the voltage of the full battery at 20mA constant current discharge for 60 minutes, an OCP test is performed for 20 minutes. The above is one cycle. After testing the full battery cycle, it can be seen that the discharge performance of the full battery is stable.

[0075] like Fig.12 As shown in the figure, the step discharge of the whole battery is performed. The overall performance of the whole battery is judged by testing the voltage stability at different currents of 1mA, 10mA, 20mA, 40mA, 60mA, 80mA, 100mA, and 20mA. Each current test is 600s. This test shows that the whole battery can still discharge stably under high current discharge, and after high current discharge, the whole battery can still maintain a stable voltage at a current of 20mA and the voltage value does not change much.

[0076] go through Figure 5-8 The catalyst test showed that the catalyst had an excellent half-wave potential of 0.8862 V (vs. RHE), a lower oxygen reduction reaction potential of 1.121 V (vs. RHE) and higher stability. Figure 9-12The full battery data after the catalyst was prepared into a cathode film also showed that the alkaline aluminum-air battery assembled with the catalyst had a good power density (60.88 mW·cm -2 ) and capacity density (1307.55mAh g -1 ), and the catalyst showed excellent stability in long-term discharge. The catalyst also showed excellent stability under various current step discharges, and was able to adapt to different currents of 1-100mA and stably maintain the operation of alkaline aluminum-air batteries.

[0077] Above Figure 1-12 The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the present invention. Anyone familiar with the technology may modify or change the above embodiments without violating the spirit and scope of the present invention. Therefore, all equivalent modifications or changes made by those with ordinary knowledge in the technical field without departing from the spirit and technical ideas disclosed by the present invention should still be covered by the claims of the present invention.

Claims

1. A method for preparing a manganese-based catalyst as a positive electrode material for an alkaline aluminum-air battery, characterized in that: The following steps are involved: (1) Preparing methylcellulose aerogel; (2) Preparation of g-C3N4; (3) Grind and mix g-C3N4, manganese dioxide, and conductive carbon black evenly, spread them on the methyl cellulose aerogel, put them into a tubular furnace for heat treatment, and then grind them to obtain a manganese-based catalyst.

2. The method for preparing the alkaline aluminum-air battery positive electrode material-manganese-based catalyst according to claim 1, characterized in that: The step (1) comprises pouring methyl cellulose slowly and repeatedly in small amounts into water, stirring evenly, placing the methyl cellulose in a refrigerator for pre-freezing after gelation, and performing freeze-drying treatment after pre-freezing to obtain methyl cellulose aerogel, wherein the gelation time is 1 day, the pre-freezing time is 3 days, and the drying time is 2 days.

3. The method for preparing the alkaline aluminum-air battery positive electrode material-manganese-based catalyst according to claim 1, characterized in that: The step (2) comprises: weighing melamine and pouring it into a porcelain boat, placing the porcelain boat in a tubular furnace for heat treatment, cooling to room temperature after the heat treatment, transferring the product in the porcelain boat into a mortar, grinding it evenly to obtain g-C3N4, and the heat treatment conditions in the tubular furnace are: heating to 550°C at a heating rate of 5°C / min and then maintaining the temperature for 4 hours.

4. The method for preparing the alkaline aluminum-air battery positive electrode material-manganese-based catalyst according to claim 1, characterized in that: In the step (3), the mass ratio of methyl cellulose aerogel: g-C3N4: manganese dioxide: conductive carbon black is 2:2:1:

1.

5. The method for preparing the alkaline aluminum-air battery positive electrode material-manganese-based catalyst according to claim 1, characterized in that: In the step (3), the heat treatment conditions in the tubular furnace are: the tubular furnace is heated to 800° C. at a heating rate of 5° C. / min and then maintained at a constant temperature for 2 hours.

6. The method for preparing the alkaline aluminum-air battery positive electrode material-manganese-based catalyst according to claim 5, characterized in that: In the step (3), argon gas needs to be continuously introduced into the tubular furnace during the heat treatment process.

7. The method for preparing the alkaline aluminum-air battery positive electrode material-manganese-based catalyst according to claim 1, characterized in that: In the step (1), the obtained methyl cellulose aerogel is cut into thin slices weighing 0.2 g.

8. An alkaline aluminum-air battery, comprising a full battery, an alkaline electrolyte and a peristaltic pump, characterized in that: The full battery includes a battery fixture, the battery fixture includes a sealing rubber gasket, a reaction chamber, and a battery template, the reaction chamber is composed of a liquid inlet pipe, a reaction chamber and a liquid outlet pipe as a whole; the sealing rubber gasket is attached to both sides of the reaction chamber, and the aluminum sheet and the positive electrode film are attached to the sealing rubber gasket, and the battery template is closed to complete a full battery assembly; The alkaline electrolyte is stored in an electrolyte storage tank and connected to a peristaltic pump through a circulation pipe; The circulation pipe is connected with the liquid inlet pipe and the liquid outlet pipe; The positive electrode membrane is composed of a waterproof breathable membrane, a nickel mesh, a waterproof breathable membrane and a catalyst layer from bottom to top, wherein the catalyst layer is a manganese-based catalyst prepared by the preparation method described in any one of claims 1-7.

9. The alkaline aluminum-air battery according to claim 8, characterized in that The alkaline electrolyte is 4 mol·L -1 of NaOH solution.

10. The alkaline aluminum-air battery according to claim 8, characterized in that The preparation of the positive electrode film comprises the following steps: (1) Weigh the corresponding materials according to the mass ratio of manganese-based catalyst: conductive carbon black: activated carbon: polytetrafluoroethylene emulsion = 2:1:4:3, first grind the manganese-based catalyst, conductive carbon black and activated carbon in a mortar evenly, then add anhydrous ethanol with a similar dry matter weight to disperse evenly, then drop the polytetrafluoroethylene emulsion into it, grind it with a grinding rod, and obtain a dough-like catalyst material with a smooth surface; (2) Pressing the dough-like catalyst material into a 0.1-0.15 mm film and drying it to form a catalyst layer; (3) stacking the waterproof breathable membrane, nickel mesh, waterproof breathable membrane and catalyst layer from bottom to top, and pressing them into a 0.3 mm positive electrode membrane using a double roller machine; (4) The positive electrode film is placed in an oxygen-free environment and subjected to high temperature treatment at 300° C. for 1-3 hours.